Modernist Aesthetics and Familial Textuality: Gide's Strait is the Gate - Roddey Reid (Studies in 20th & 21st Century Literature, 1989)
The essay explores different links drawn by Edward Said and Jean Bone between early modernist fiction and what they call bachelor literature or discourse. The latter attempted to break free from the bourgeois ideology of the family as constituted in the late 18th and early 19th centuries. Modernist fiction is anti-bourgeois and anti-familial in some of its deepest impulses. In Strait is the Gate Jerome's narrative is a tale of failed courtship that has as its setting bourgeois family life in a stage of dissolution. Out of the overwrought family drama emerges an aesthetic problematic: Jerome's account of a fragmented narrative that eschews the traditional orderings of the récit. Moving beyond traditional Freudian interpretations with their Oedipal infrastructure (the death of Jerome's father, etc.) the present work analyzes how the narrative of the genesis of the modernist writer is decisively mediated by stories about women and by feminine writing. In a sense, a mother's story—that of Aunt Lucile—and her daughters'—that of Alissa—are two poles of the novel's trajectory that traverses Jerome and constitutes him as a complexly gendered writing subject. Like Jerome, the novel is divided against itself on the question of the feminine. Indeed, the narrative's simultaneous, contradictory appropriation and negation of the feminine (the incorporation of Alissa's correspondence and the progressive elimination of all female characters except for Juliette) defines its fundamental structure as hysterical. This structure is the vehicle for the deployment of a complex fictional strategy by Gide whereby he constructs a presentation of familialism's radical other: the bachelor writer whose possible homosexuality is approached asymptotically and negatively by the text through what are ultimately paranoiac figurations of other familial outcasts. These narrative figurations restore a discursive continuity to an otherwise fragmented modernist text, a continuity that is paradoxically none other than that of familial discourse.
Keywords: Edward Said; Jean Bone; André Gide; modernist fiction; early modernist fiction; bachelor literature; discourse; bourgeois ideology; family; late 18th and early 19th centuries; 18th; 19th; century; Modernist fiction; fiction; modernist; anti-bourgeois; anti-familial; Strait is the Gate; Jerome; failed courtship; bourgeois family life; family drama; fragmented narrative; récit; traditional Freudian interpretation; Freudian; Freud; Oedipal; death of Jerome; death; father; narrative; genesis; modernist writer; women; feminine writing; mother' s story; Aunt Lucile; daughter; Alissa; poles; feminine; appropriation; negation; correspondence; female characters; Juliette; structure; Gide; familialism; radical other; other; homosexuality; asymptotically; paranoiac; modernist text